The Concept of Resistance according to Giorgio Agamben - المحمد ‏‪محسن; هلا علي; جلال بدلة (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
This paper seeks to identify the philosophical foundations of the concept of resistance and its forms according to the Italian philosopher Giorgio Agamben. Because this requires first identifying the forces that resistance must confront, the paper concerns initially with clarifying the concept of apparatus according to Agamben, which the resistance that he establishes aims to confront. After that, the paper begins to clarify the basis on which the concept of resistance is based, which is the concept of potentiality, especially the Potentiality-not-to do (impotentiality). Agamben thought about the basic relationship between potentiality and impotentiality according to Aristotle and his commentators. He produced the concept of inoperativity. From all of these concepts emerged the concept of resistance as an opposition to internal and external forces that work to disrupt the capitalist apparatuses that aim to capture, stereotype, regulate and control human beings, and which seek to prevent people and their ability to act and not to act, especially preventing the latter because it thus paralyzes the ability to resist and frustrates its emergence. In the final analysis, according to Agamben, resistance seeks to restore the inherent dimension of the human being that distinguishes him from the rest of beings, which is the dimension of potentiality, especially in its form of the ability to not act.